FEATURES OF THE COURSE OF THE NEONATAL PERIOD OF PREMATURE INFANTS BORN AT 28 TO 32 WEEKS, WHOSE INTESTINES ARE COLONIZED BY KLEBSIELLA PNEUMONIAE WITH DIFFERENT SETS OF GENES - Анна Алексеевна Маханёк; Гузель Нуховна Чистякова; Александр Владимирович Устюжанин; Ирина Ивановна Ремизова (The Publishing House Medicine and Enlightenment, 2023)
The aim of the research - to evaluate the features of the neonatal period of premature infants born at 28 weeks to 32 weeks, whose intestines are colonized by Klebsiella pneumoniae with a different set of genes. Materials and methods. A clinical and laboratory examination of 25 newborns of gestational age 28-32 weeks, whose intestines were colonized by KP, was carried out. Depending on the genovariant of the strains, the children were divided into three groups: group 1 - premature, colonized by the KP gene uge (n = 6), 2nd - uge + fim (n = 12), 3rd - kfu + uge + fim (n = 7). Results. The article presents data on the course of the neonatal period in children with CD with a different set of genes. It was shown that the anthropometric data at birth in all three groups were comparable, the Apgar score was lower in children colonized by KP with uge + fim genes. Premature newborns with KP uge+ had a smaller number of clinical manifestations. The leading symptoms in groups 2 and 3 were flatulence and regurgitation. It is shown that the observed children who secrete KR - with two and three virulence factor genes with feces have lower red blood counts. In the studied newborn carriers of CD with an isolated uge gene, the pathogen eradication occurred in a hospital setting, and in most cases they were discharged with a more diverse intestinal microbiocenosis due to the presence of other representatives of the microbiota, unlike children of the 2nd and 3rd groups. Conclusion. Taking into account the functional immaturity of the immune system of premature infants and the impact of exogenous factors, in particular CD, children colonized by this strain with the genetic profile of uge + fim and kfu + uge + fim constitute a risk group for the implementation of klebsiella infection. Therefore, further clinical observation is necessary for patients who are bacterial isolators.